2007
DOI: 10.4321/s0365-66912007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Edema bilateral del nervio óptico por leucemia linfocítica crónica

Abstract: Leukaemic infiltration of the optic nerve and central nervous system is a rare complication of chronic lymphocytic leukaemia, although it is common in the acute forms of this disease. Optic nerve infiltration is the most important ophthalmologic manifestation of leukaemia because it threatens vision and it is treatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several reports exist concerning the relationship between papilledema and acute myeloid leukemia,[526] acute lymphoblastic leukemia,[7911174752] chronic myelogenous leukemia,[14] and chronic lymphocytic leukemia. [39] In a study of 82 children with acute leukemia, Reddy et al . [37] found that only 3 children complained of eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports exist concerning the relationship between papilledema and acute myeloid leukemia,[526] acute lymphoblastic leukemia,[7911174752] chronic myelogenous leukemia,[14] and chronic lymphocytic leukemia. [39] In a study of 82 children with acute leukemia, Reddy et al . [37] found that only 3 children complained of eye symptoms.…”
Section: Discussionmentioning
confidence: 99%